2009
DOI: 10.1128/iai.00994-08
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell and NK Cell Reciprocal Cross Talk Promotes Gamma Interferon-Dependent Immunity to Blood-StagePlasmodium chabaudiAS Infection in Mice

Abstract: Dendritic cells (DCs) are important accessory cells for promoting NK cell gamma interferon (IFN-␥) production in vitro in response to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 46 publications
3
88
0
2
Order By: Relevance
“…A line of evidence indicates that NK cells can regulate DC function and that NK-DC cross-regulation plays an important role in dictating the quality and the quantity of the adaptive immune responses (16)(17)(18)(19)(20)(21). A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via the NKG2D receptor pathway (21).…”
mentioning
confidence: 99%
“…A line of evidence indicates that NK cells can regulate DC function and that NK-DC cross-regulation plays an important role in dictating the quality and the quantity of the adaptive immune responses (16)(17)(18)(19)(20)(21). A recent study showed that NK cells can enhance the capacity of DC to present parasitic Ags via the NKG2D receptor pathway (21).…”
mentioning
confidence: 99%
“…NK cells display powerful cytotoxic activities once activated, and are potent producers of pro-inflammatory cytokines including IFN-γ and TNF-α which can contribute to the modulation of adaptive immune responses and direct anti-tumour effects (99)(100)(101) . In the context of inflammatory disease, NK cells have been implicated in the pathogenesis of inflammatory bowel disease and psoriasis (102,103) .…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…Virtually all NK cells in the LN belong to the CD56 bright CD16 2 compartment [35], which respond very efficiently to DC-derived cytokines by proliferation and IFN-c production [33,[36][37][38][39][40][41]. In turn, IFN-c promotes DC maturation and sustains Th1 immune responses by providing a conditioning signal that increases the capacity of DC to produce interleukin (IL)212 [21][22][23]42]. In contrast, the CD56 dim CD16 1 NK cell subset enriched in peripheral blood expresses homing receptors for inflamed tissues and rapidly mediates cytotoxicity, which can be enhanced by DC-derived IL-12 [38,41].…”
Section: Introductionmentioning
confidence: 99%
“…In the early phases of an immune response, DC encounter LN-NK cells, that is, before antigen-driven activation of na€ ıve T cells [23,34]. NK cells comprise various subsets that differ in function, phenotype, and tissue localization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation